Teledentistry and its applications in paediatric dentistry: A literature review. Issue 3 (December 2021) - Sharma, Harshita; Suprabha, Baranya Shrikrishna; Rao, Arathi
Abstract: Background: During the unfortunate event of the COVID-19 pandemic, restrictions were placed on face-to-face interactions in dentistry to promote social distancing and reduce spread of virus. In order to provide dental services teledentistry was employed. Objective: This article aims to review the literature and information available on the provision and utilization of teledentistry as a method to address oral health needs of paediatric patients. Results: Teledentistry has been utilised in paediatric population for the purpose of oral health education and promotion, remote diagnosis and monitoring, and behaviour guidance. Studies involving paediatric population for aforementioned applications have shown that this practice strategy is beneficial to provide dental treatment in remote locations with little access to paediatric dental specialists, monitor patients between appointments, conduct remote diagnosis and screening programmes, promote oral health of children through dental education, and in pre-appointment behaviour guidance. This method was particularly useful during the current COVID-19 pandemic where dentists use their mobile phones, computer webcams for patient appointments while maintaining safe distance and avoid exposing themselves as well as patient to the virus. Conclusion: Teledentistry can be a supplement to face-to-face methods of paediatric dental care, ultimately leading to better patient management. This technology can make a significant contribution in reducing the supply-demand gap of paediatric dental specialists in places where healthcare facilities are limited and ensure safety during the pandemic whilst providing dental care to paediatric patients. Further research is required for safe, effective and evidence-based use of teledentistry in the field of paediatric dentistry.